2009
DOI: 10.1112/s0010437x0900431x
|View full text |Cite
|
Sign up to set email alerts
|

On the probabilities of local behaviors in abelian field extensions

Abstract: For a number field K and a finite abelian group G, we determine the probabilities of various local completions of a random G-extension of K when extensions are ordered by conductor. In particular, for a fixed prime ℘ of K, we determine the probability that ℘ splits into r primes in a random G-extension of K that is unramified at ℘. We find that these probabilities are nicely behaved and mostly independent. This is in analogy to Chebotarev's density theorem, which gives the probability that in a fixed extension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 24 publications
5
88
0
Order By: Relevance
“…The author is also aware of upcoming results for D4 Ă S8 [SV19] and a large family of imprimitive groups (including many wreath products of the form T ≀ B for T abelian or S3) [LOWW19]. Similar results are known when the extensions L{K are ordered by other invariants, for example Wood [Woo09] proves the analogous results for abelian groups ordered by conductor. The constant cpK, Gq, while known to be positive in all of the above cases, is known explicitly in far fewer cases, such as for abelian extensions over Q by Mäki [Ma85] and cyclic quartic extensions over general K by Cohen-Diaz y Diaz-Olivier [CDyDO05].…”
Section: Introductionmentioning
confidence: 65%
“…The author is also aware of upcoming results for D4 Ă S8 [SV19] and a large family of imprimitive groups (including many wreath products of the form T ≀ B for T abelian or S3) [LOWW19]. Similar results are known when the extensions L{K are ordered by other invariants, for example Wood [Woo09] proves the analogous results for abelian groups ordered by conductor. The constant cpK, Gq, while known to be positive in all of the above cases, is known explicitly in far fewer cases, such as for abelian extensions over Q by Mäki [Ma85] and cyclic quartic extensions over general K by Cohen-Diaz y Diaz-Olivier [CDyDO05].…”
Section: Introductionmentioning
confidence: 65%
“…Ellenberg and Venkatesh [2005, Section 4.2] suggest that we can try to count extensions of global fields by quite general invariants of Galois representations. In [Wood 2008], it is shown that when counting by certain invariants of abelian global fields, such as conductor, Bhargava's question can be answered affirmatively. It is also shown in [Wood 2008] that when counting abelian global fields by discriminant, the analogous conjectures fail in at least some cases.…”
Section: Introductionmentioning
confidence: 99%
“…In [Wood 2008], it is shown that when counting by certain invariants of abelian global fields, such as conductor, Bhargava's question can be answered affirmatively. It is also shown in [Wood 2008] that when counting abelian global fields by discriminant, the analogous conjectures fail in at least some cases. In light of the fact that Bhargava's conjectures for the asymptotics of the number of S n -number fields arise from his mass formula (1-1) for counting by discriminant, one naturally looks for mass formulas that use other ways of counting, such as Theorem 1.1, which might inspire conjectures for the asymptotics of counting global fields with other Galois groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon of different orderings on the same set of number fields plays a prominent role in asymptotic studies [32]. Here we are interested instead in initial segments and how they depend on χ.…”
Section: Different Orders On the Same Set Of Fieldsmentioning
confidence: 99%